2003
DOI: 10.1074/jbc.m212491200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of PTP1B Complexed with a Potent and Selective Bidentate Inhibitor

Abstract: Protein-tyrosine phosphatase 1B (PTP1B) has been implicated as an important regulator in several signaling pathways including those initiated by insulin and leptin. Potent and specific PTP1B inhibitors could serve as useful tools in elucidating the physiological functions of PTP1B and may constitute valuable therapeutics in the treatment of several human diseases. We have determined the crystal structure of PTP1B in complex with compound 2, the most potent and selective PTP1B inhibitor reported to date. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
142
2
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 142 publications
(153 citation statements)
references
References 44 publications
5
142
2
4
Order By: Relevance
“…In this context, it is of interest that an elegant study demonstrated that Arg-47 can adopt one of two conformations and thus accommodate different substrates that bind to this part of PTP1B. Indeed, several PTP1B inhibitors have been shown to address Arg-47 (18,22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, it is of interest that an elegant study demonstrated that Arg-47 can adopt one of two conformations and thus accommodate different substrates that bind to this part of PTP1B. Indeed, several PTP1B inhibitors have been shown to address Arg-47 (18,22).…”
Section: Discussionmentioning
confidence: 99%
“…However, in this case molecular modeling indicated that position 5 in OATP would be more attractive for introducing substituents that could address the region defined by residues 47 and 48. Of note, a highly selective and potent PTP1B inhibitor that simultaneous binds to the active site and both residues was recently described (22). Therefore, our goal was to introduce substituents into OATP that would bind PTP␤ with high affinity and PTP1B with lower affinity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphatase Assay-Initial rate measurements for the Lypcatalyzed p-nitrophenyl phosphate hydrolysis were carried out as described (22,23). The Lyp-catalyzed hydrolysis of Tyr(P)-containing peptides was continuously monitored at 305 nm for the increase in tyrosine fluorescence with excitation at 280 nm (18 Peptide Synthesis and Characterization-The synthesis and characterization of the inverse alanine phosphopeptide library were described previously (18).…”
Section: Methodsmentioning
confidence: 99%
“…The x-ray structure of PTP1B bound to an effective competitive inhibitor [Protein Data Bank (PDB) ID code 1N6W (27)] was used as a template. In the resulting model of Shp2, the active center appears as a deep and narrow substrate-binding pocket (Fig.…”
Section: Identification Of the Phps Compound Class Of Shp2 Inhibitorsmentioning
confidence: 99%